THEOKRASI DALAM KITAB MIKHA DAN HUBUNGANNYA DENGAN PERAN PEMIMPIN GEREJA DAN PEMERINTAHAN DALAM UPAYA PEMBERANTASAN KELOMPOK KRIMINAL BERSENJATA (KKB) PAPUA - Lumintang, Sheline Feranda (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
This research aims to examine how God's sovereignty described in the book of Micah relates to church and government leaders who are God's tools or representatives to eradicate the Armed Criminal Group (KKB) in Papua whose actions are explicitly opposed by God. This research is based on library research. In addition, a content analysis will be conducted which includes an in-depth discussion of information written or printed in various media. The researcher summarizes the pattern of God's Theocracy in the form of a diagram to make it easier for readers to understand the pattern of God's Theocracy through the prophet Micah and also the pattern of God's Theocracy through church and government leaders. In the book of Micah, the Theocracy of God is seen from the role of the Prophet Micah in his time who was angry at the problems that occurred in the Israeli and Judah nation.